1997
DOI: 10.1038/sj.sc.3100504
|View full text |Cite
|
Sign up to set email alerts
|

SCIM – spinal cord independence measure: a new disability scale for patients with spinal cord lesions

Abstract: The Spinal Cord Independence Measure (SCIM) is a new disability scale developed speci®cally for patients with spinal cord lesions in order to make the functional assessments of patients with paraplegia or tetraplegia more sensitive to changes. The SCIM includes the following areas of function: self-care (subscore 0 ± 20), respiration and sphincter management (0 ± 40) and mobility (0 ± 40). Each area is scored according to its proportional weight in these patients' general activity. The ®nal score ranges from 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
332
0
18

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(355 citation statements)
references
References 6 publications
5
332
0
18
Order By: Relevance
“…The extent to which these patients can use their hands represents a measure of their independence, which is commonly assessed by scores in ADL, such as the Functional Independence Measurements (FIM) and Spinal Cord Independence Measure (SCIM). 36 These measures are also used to determine the extent of support and assistance the patient would need during the day, and in how far the accommodation and employment environment have to be adapted to ®t the patient's needs.…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…The extent to which these patients can use their hands represents a measure of their independence, which is commonly assessed by scores in ADL, such as the Functional Independence Measurements (FIM) and Spinal Cord Independence Measure (SCIM). 36 These measures are also used to determine the extent of support and assistance the patient would need during the day, and in how far the accommodation and employment environment have to be adapted to ®t the patient's needs.…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…The K-B Scale measures basic ADL divided into essential components (items) of an activity. This is an advantage over other known ADL scales 19,39,40 as it makes it possible to detect problematic items within dimensions and thus makes it a better tool for target interventions in ADL in patients with cervical SCI regardless of functional level.…”
Section: Discussionmentioning
confidence: 99%
“…56 Earlier studies have shown that diagnosis-specific scales such as the Spinal Cord Independence Measure (SCIM) 40 and the QIF 19 are more sensitive to small changes in a patient's ability to perform ADL and therefore better reflect rehabilitation outcome in cervical SCI patients than FIMt. 39 However, SCIM and QIF have items that lack requirements to assess important components of an activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the shortform QIF score correlated with the Upper Extremity Motor Score (r40.8); 32 the SCIM with the FIM (r40.8), 33,54 the WISCI (r ¼ 0.97) 38 and with the NAC (r ¼ 0.47-0.85). 40 Considerable evidence of convergent validity was presented for the WISCI: with the FIM (rX0.7), 36,38 the LEMS(r ¼ 0.47-0.91), 58 the Berg Balance Scale, 57 the BI and Rivermead mobility index (both r ¼ 0.67), 38 and the SCIM (r ¼ 0.97).…”
Section: Measurement Properties Of Instruments Within the Sci Contextmentioning
confidence: 91%
“…The SIP68 has also been evaluated with SCI patients in two studies with relatively large sample sizes. 45,46 Instruments that were designed specifically to assess the function or mobility of SCI patients are: the Quadriplegia Index of Function (QIF) 31,30 and Short-form QIF; 32 the Spinal Cord Independence Measure (SCIM) 33 and Catz-Itzkovich revised SCIM; 35 the Walking Index for Spinal cord injury (WISCI); 36 the Needs Assessment Checklist (NAC), 40 and the Spinal Cord Injury Functional Ambulation Inventory (SCI-FAI). 43 Item generation.…”
Section: Instrumentsmentioning
confidence: 99%